Racial and Ethnic Differences in Emergency Department Utilization and Diagnosis for Sports-Related Head Injuries - Lyons, Todd W.; Miller, Kelsey A.; Miller, Andrew F.; Mannix, Rebekah (Frontiers in Neurology, 2019)
Background: Prior studies have shown racial differences in concussion awareness and outcome. Objective: To assess if racial or ethnic differences exist in Emergency Department (ED) utilization and diagnosis for children with sports-related head injuries. Methods: We performed a retrospective, cross-sectional analysis of ED visits from 2008-2017 using National Electronic Injury Surveillance System data. Population-weighted ED visits for children age 7-18 years with a sport-related injury were included. We compared the probability of an ED visit being for an injury to the head or diagnosed as a concussion between children of different races/ethnicities. Analyses were adjusted for age, gender, sport, year and location where the injury occurred. Results: We identified 11,529,994 population-weighted ED visits for pediatric sports-related injuries, of which 1,497,717 (13.0%) were injuries to the head and 619,714 (5.4%) received a diagnosis of concussion. Black children were significantly less likely than non-Hispanic white children to have their ED visit be for an injury to the head [Odds Ratio (OR) 0.72, 95%CI 0.65-0.79] or concussion (OR 0.58, 95%CI 0.50-0.68). Black children presenting to the ED with an injury to their head were less likely than non-Hispanic white children to be diagnosed with a concussion (OR = 0.71, 95%CI 0.59-0.85). Conclusions: Racial differences exist in both ED utilization for pediatric sports-related head injuries and in the diagnosis of concussion. Further work is needed to understand these differences to ensure all brain injured athletes receive optimal care, regardless of race.